2017
DOI: 10.1002/2016jb013761
|View full text |Cite
|
Sign up to set email alerts
|

Bottom‐simulating reflector dynamics at Arctic thermogenic gas provinces: An example from Vestnesa Ridge, offshore west Svalbard

Abstract: The Vestnesa Ridge comprises a >100 km long sediment drift located between the western continental slope of Svalbard and the Arctic mid‐ocean ridges. It hosts a deep water (>1000 m) gas hydrate and associated seafloor seepage system. Near‐seafloor headspace gas compositions and its methane carbon isotopic signature along the ridge indicate a predominance of thermogenic gas sources feeding the system. Prediction of the base of the gas hydrate stability zone for theoretical pressure and temperature conditions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(101 citation statements)
references
References 90 publications
2
99
0
Order By: Relevance
“…We note a discrepancy between computed BGHSZ and observed BSR depth with a misfit up to 100 m (Figures c and d). Previous studies focused on investigating the cause of BGHSZ/BSR mismatch on different margins (Flemings et al, ; Hornbach et al, ; Plaza‐Faverola et al, ; Xu & Ruppel, ). Phrampus et al (), for instance, observed a similar phenomenon on the upper U.S. Beaufort margin, and the discrepancy was mainly attributed to significant warming of intermediate ocean temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We note a discrepancy between computed BGHSZ and observed BSR depth with a misfit up to 100 m (Figures c and d). Previous studies focused on investigating the cause of BGHSZ/BSR mismatch on different margins (Flemings et al, ; Hornbach et al, ; Plaza‐Faverola et al, ; Xu & Ruppel, ). Phrampus et al (), for instance, observed a similar phenomenon on the upper U.S. Beaufort margin, and the discrepancy was mainly attributed to significant warming of intermediate ocean temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…For the case of the Western Black Sea, we explore four main hypotheses that may explain that the observed BSRs is deeper than the predicted steady state BGHSZ: different composition of gas or water than the ones measured in situ and used in the calculation of the thermodynamic stability of gas hydrates (Dickens & Quinby‐Hunt, ; Plaza‐Faverola et al, ; Popescu et al, ), inaccurate geothermal gradient values and possible spatial variation (Grevemeyer & Villinger, ; Minshull & Keddie, ; Yamano et al, ), a transient state of the hydrate system related to the nonequilibrium of the thermal regime (Phrampus et al, ), and a transient state of the hydrate system related to the excess pore pressure generated by hydrate dissociation. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seafloor pockmarks and gas chimneys along the ridge are linked to faults and fractures (Plaza‐Faverola et al, ; Singhroha et al, ). Considering the suggested presence of thermogenic gas (Panieri et al, ; Plaza‐Faverola et al, ; Smith et al, ) in the study area, the study of fault/fracture systems is even more important as thermogenic gases have deeper origins (often below the GHSZ) and structural features affect the migration pathways of thermogenic gases. Faults at deeper depths in this region can be potential fluid migration pathways for deep sourced warm fluids (Knies et al, ; Dumke et al, ; Waghorn et al, ), whereas faults at the shallower depths within the GHSZ can be migration pathways or can also act as seals, as they can potentially be plugged with gas hydrates (Goswami et al, ; Madrussani et al, ).…”
Section: Study Areamentioning
confidence: 99%
“…In quiescent environments where hydrate has sufficient time to equilibrate with water (Ebinuma et al, ; Hyodo et al, ; Kneafsey et al, ), such compositional details have been shown to diminish over time through diffusion in order to establish hydrate‐water equilibrium (Circone et al, ). However, in environments where hydrate formation is being fed by active gaseous methane flow, such as that of hydrated‐crusted gas bubble plumes (Wang et al, ), seeps, and seafloor outcrops (Bünz et al, ; Haeckel et al, ; Linke et al, ; Macelloni et al, ; Plaza‐Faverola et al, , , Riedel et al, ; Suess et al, ; Smith et al, ), and gas chimneys (Andreassen et al, ; Haeckel et al, ; Liu & Flemings, ), the compositional gradient in the hydrate is likely sustained by the nonequilibrium nature of interfacial hydrate formation. While in situ measurements of hydrate compositions in these environments are less accessible, our results suggest that xenon is a good laboratory analog to methane in order to understand how hydrate formers transport through these geologic multiphase settings.…”
Section: Discussionmentioning
confidence: 99%